2011
DOI: 10.1029/2010jd015154
|View full text |Cite
|
Sign up to set email alerts
|

Free tropospheric ozone changes over Europe as observed at Jungfraujoch (1990–2008): An analysis based on backward trajectories

Abstract: [1] High-altitude ozone measurements at the Jungfraujoch observatory, Switzerland (JFJ, 3850 asl), covering the period 1990-2008 are investigated in this study. Anthropogenic ozone precursor emissions decreased over Europe and North America since the early 1990s. However, ozone concentrations at JFJ over the 19 year period show significant positive trends in the 1990s and no significant trends after 1999. Ozone trends were further studied with respect to air mass origin using 20 day back trajectories. The ozon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 58 publications
4
54
0
Order By: Relevance
“…We did not observe any significant long-term trend in the source regions over the years (not shown), although a year to year variability is present (Cui et al, 2011). Also a seasonal difference was clearly noticeable.…”
Section: Identification Of Source Regionsmentioning
confidence: 73%
“…We did not observe any significant long-term trend in the source regions over the years (not shown), although a year to year variability is present (Cui et al, 2011). Also a seasonal difference was clearly noticeable.…”
Section: Identification Of Source Regionsmentioning
confidence: 73%
“…The Mace Head data analyzed here have been filtered to remove recent European influence [see Parrish et al, 2012]. A separate analysis of a Jungfraujoch data set that was similarly filtered [Cui et al, 2011] yields a seasonal shift statistically consistent with those shown in Figure 2a. Although these sites provide only sparse coverage of the northern midlatitudes, the sites do represent baseline (here understood as representative of continental to hemispheric scales) O 3 [Parrish et al, 2012], so we hypothesize it is a hemisphere-wide phenomenon.…”
Section: Resultsmentioning
confidence: 99%
“…3) that may be related to e.g., local wind systems (Zellweger et al, 2000). Cui et al (2011) found for example that summer convective boundary layer can reach the altitudes of Jungfraujoch during highpressure conditions (resulting in high ozone concentrations in 2003), which could balance the effect of a decrease in European precursor emissions.…”
Section: Low Percentilesmentioning
confidence: 99%